The Aspirations of the Indonesian Nation in Anis Matta's Speech “Kullunā Fālāstīn” Critical Discourse Analysis Norman Fairclough's Theory - Mustofa, Rifki; Zawawi, Moh (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
The escalating conflict between Israel and Palestine has become a major focus of international forums, including the Organization of Islamic Cooperation (OIC) Summit and the Arab League held in Riyadh, Saudi Arabia, on November 11, 2024. In this conference, Indonesia played an active role through a speech delivered by Deputy Minister of Foreign Affairs, Anis Matta. This study aims to explore how Indonesia’s national aspirations are represented in the speech, how the text is interpreted by various audiences, and how sociocultural contexts contribute to the meaning of the speech. Types of research in this study are descriptive qualitative, Identify Subsections consists of the primary data source is the transcription of Anis Matta’s speech, supported by relevant journal articles, books, and literature. Data collection techniques include watching and note-taking. The data is analyzed using Norman Fairclough’s critical discourse analysis model: textual analysis, discourse practice, and sociocultural practice. The findings indicate that the speech represents Indonesia’s aspirations through various statements, including highlighting Israel’s acts of genocide, criticism of the lack of unity among Islamic countries, a proposal of five strategic steps and others. The speech produced in the context of escalating Israel-Palestine conflict and received positive responses from the public. Influential sociocultural factors include institutional, situational, and systemic aspects such as politics, history, and culture. This research contributes to Arabic language studies and critical linguistics by showing how language in diplomacy can reflect national values in international forums, especially amid the intensifying Palestine-Israel conflict. However, the study is limited by its focus on a single speech and suggests future research to include comparative analysis and assess the concrete impact on Indonesia’s foreign policy.